2023
DOI: 10.1038/s41598-023-44119-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations among the workplace violence, burnout, depressive symptoms, suicidality, and turnover intention in training physicians: a network analysis of nationwide survey

Je-Yeon Yun,
Sun Jung Myung,
Kyung Sik Kim

Abstract: Depression and anxiety are the most common mental disorders among physicians, who have a greater risk of suicide than those in other professional occupations. Relationships among a demanding workload, workplace violence, burnout, and intention to turnover have also been reported. The current study examined the principal components and propagating patterns of mental health and working environment interactions in training physicians. A total of 1981 training physicians completed online self-report questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 117 publications
0
3
1
Order By: Relevance
“…While depression independently increased the odds of suicidality by about 5-6 times 30 , as depression intensi es, the association between workplace bullying and suicide may weaken. Unlike previous research suggesting that workplace bullying might lead to suicidal thoughts and attempts via signi cant mood disorders 7,29 , this study indicates that workplace bullying itself might directly progress to suicide attempts. According to the Integrated Motivational-Volitional (IMV) model, after exposure to bullying, suicide attempts occur, which progress through three stages: phase 1-the premotivational phase of exposure to background factors and triggering events; phase 2-the motivational phase of repeated bullying leading to suicidal intent formation; and phase 3-the volitional phase of increased suicidal thoughts transitioning to attempts 49 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While depression independently increased the odds of suicidality by about 5-6 times 30 , as depression intensi es, the association between workplace bullying and suicide may weaken. Unlike previous research suggesting that workplace bullying might lead to suicidal thoughts and attempts via signi cant mood disorders 7,29 , this study indicates that workplace bullying itself might directly progress to suicide attempts. According to the Integrated Motivational-Volitional (IMV) model, after exposure to bullying, suicide attempts occur, which progress through three stages: phase 1-the premotivational phase of exposure to background factors and triggering events; phase 2-the motivational phase of repeated bullying leading to suicidal intent formation; and phase 3-the volitional phase of increased suicidal thoughts transitioning to attempts 49 .…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, population-based studies utilizing national patient registers in countries like Australia, Denmark, Sweden, and Japan consistently indicated that exposure to workplace bullying heightened the risk of suicidal ideation 8-10,14,39 . In contrast, within Korea, studies exploring the connection between bullying and suicide predominantly focused on vulnerable groups like adolescents, the elderly, or speci c occupations such as nursing, or physicians-in-training [27][28][29] . This study, harnessing health examination data from a healthy cohort of Korean employees, not only represented the o ce workforce but also examined exposure frequency, a realm previously underexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the increasing cases of violence and abuse against healthcare professionals, poor working conditions and environment, in conjunction with the poor economic situation, as well as increased anxiety and depression among working physicians and nurses, there is an increased possibility of heightened fear of the spread of suicidal ideation or suicide (41,42). Olwan and Alsawalqa (43) confirmed that the number of Jordanians who committed suicide over the study period was 1,119, and most cases occurred in the capital city, Amman.…”
Section: Discussionmentioning
confidence: 99%